Relationships between Popovych's Adaptation Index and parameters of ongoiging HRV and EEG in patients with chronic pyelonephrite and cholecystite in remission - Stepan V. Petsyukh; Marta S. Petsyukh; Marta M. Kovbasnyuk; Liliya G. Barylyak; Walery Zukow (Kazimierz Wielki University, 2016)
Petsyukh Stepan V., Petsyukh Marta S., Kovbasnyuk Marta M., Barylyak Liliya G., Zukow Walery. Relationships between Popovych's Adaptation Index and parameters of ongoiging HRV and EEG in patients with chronic pyelonephrite and cholecystite in remission. Journal of Education, Health and Sport. 2016;6(2):99-110. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.46076 http://ojs.ukw.edu.pl/index.php/johs/article/view/3382 https://pbn.nauka.gov.pl/works/714487   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.01.2016. Revised 12.01.2016. Accepted: 31.01.2016.     RELATIONSHIPS BETWEEN POPOVYCH'S ADAPTATION INDEX AND PARAMETERS OF ONGOIGING HRV AND EEG IN PATIENTS WITH CHRONIC PYELONEPHRITE AND CHOLECYSTITE IN REMISSION   Stepan V. Petsyukh1, Marta S. Petsyukh2, Marta M. Kovbasnyuk4, Liliya G. Barylyak3,4, Walery Zukow5   1Medical Rehabilitation Center "Perlyna Prykarpattya" Ministry of Internal Affairs, Truskavets', Ukraine     petsyukh.s@gmail.com 2Danylo Halyts'kyǐ National Medical University, L'viv, Ukraine 3JSC "Truskavets'kurort", Truskavets', Ukraine   lgbarylyak@gmail.com 4Laboratory of Experimental Balneology, OO Bohomolets' Institute of Physiology NAS, Truskavets', Kyiv     i.popovych@ukr.net 5Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland   w.zukow@ukw.edu.pl   Abstracts Background. The conception of general adaptation reactions of organism (GARO), created by Garkavi LKh, Kvakina ЕB and Ukolova MA in 1977 on the base of Selye H classic conception of stress and developed then by them (1998), and also by Radchenko ОМ (2004), sufficiently successfully used in medicine and valeology for the estimation of general condition of organism. The downside the concept was qualitative assessment of GIRO. So Popovych IL (2000, 2006) proposed to quantify the various GARO Adaptation Index, which significantly correlated with the levels of key hormones adaptation and HRV parameters as well as phagocytosis. Another disadvantage of the concept is the lack of EEG markers GARO. We set a goal to analyze the relationships Popovych's Adaptation Index with parameters of HRV and EEG. Methods. In basal conditions in 22 men, patients with chronic pyelonephrite and cholecystite in remission, recorded twice during 9-11 days HRV ("Cardiolab+VSR", KhAI Medica, Ukraine) and EEG ("NeuroCom Standard", KhAI Medica, Ukraine). In portion of blood counted up leukocytogram, on the basis of which determined Popovych's Adaptation Index (PAI). Results. Registered 14 normal (harmonious) GARO, 20 premorbidic (disharmonious) GARO and only 9 reactions of superactivation, in the absence stress-reactions. Revealed the closest relationship between PAI and normalized Power Spectral Density (PSD) LF (r=0,44), Baevskiy's Stress Index in Orthostase (r=0,41), Laterality Index PSD θ-Rhythm (r=-0,43), PSD β-Rhythm in Right Occipital locus (r=-0,40). Canonical correlation between PAI, on the one hand, and the parameters of HRV and EEG, on the other hand, is strong: R=0,846; R2=0,716; Adjusted R2=0,628; F(10)=8,1; χ2(10)=47,3; p<10-5. Conclusion. Popovych's Adaptation Index reflects the activity of a number of regulatory nerve structures. Keywords: general adaptation reactions, leukocytogram, index of adaptation by Popovych, HRV, EEG, correlations.